Sustainable ammonia production through process synthesis and global optimization. Issue 7 (27th December 2018) - Demirhan, C. Doga; Tso, William W.; Powell, Joseph B.; Pistikopoulos, Efstratios N.
Abstract : Current ammonia production technologies have a significant carbon footprint. In this study, we present a process synthesis and global optimization framework to discover the efficient utilization of renewable resources in ammonia production. Competing technologies are incorporated in a process superstructure where biomass, wind, and solar routes are compared with the natural gas‐based reference case. A deterministic global optimization‐based branch‐and‐bound algorithm is used to solve the resulting large‐scale nonconvex mixed‐integer nonlinear programming problem (MINLP). Case studies for Texas, California, and Iowa are conducted to examine the effects of different feedstock prices and availabilities. Results indicate that profitability of ammonia production is highly sensitive to feedstock and electricity prices, as well as greenhouse gas (GHG) restrictions. Under strict 75% GHG reductions, biomass to ammonia route is found to be competitive with natural gas route, whereas wind and solar to ammonia routes require further improvement to compete with those two routes. © 2018 American Institute of Chemical Engineers AIChE J, 65: e16498 2019